Strategic Governance Architecture Under Persistent Market Volatility: A Conceptual Framework - Safroni Isrososiawan (Manexia: Journal of Business, Management, and Creative Economy, 2025)
This study develops a conceptual framework of strategic governance architecture to explain how corporate governance systems can stabilize strategic decision-making under persistent market volatility. Drawing on corporate governance, strategic management and uncertainty literature, the paper reconceptualizes governance as an integrated architecture composed of oversight depth, temporal orientation, risk framing logic and accountability discipline. Rather than treating governance as a monitoring mechanism designed primarily to mitigate agency costs, the framework positions governance as a systemic stabilizer of managerial discretion under sustained ambiguity. The analysis identifies recurring governance failure patterns – reactive overcorrection, narrative capture, passive oversight and incentive distortion – and explains these as outcomes of architectural misalignment rather than absence of formal control. The study further proposes a governance activation cycle through which persistent market volatility triggers structured recognition, interpretive deliberation, exposure calibration and strategic posture stabilization. By reframing volatility as a constitutive governance condition, the paper extends corporate governance theory beyond agency control and integrates it with strategic management perspectives on uncertainty, resilience and disciplined recalibration in turbulent markets.